In situ biogas upgrading and enhancement of anaerobic digestion of cheese whey by addition of scrap or powder zero-valent iron (ZVI) - Charalambous, Panagiotis; Vyrides, Ioannis (My University, 2021)
Cheese whey is an easily biodegradable substrate with high organic matter that can be anaerobically digested to biogas; however, the process is often inhibited by excess acidification due to the presence of undissociated volatile fatty acids and requires considerable concentration of alkaline buffer. The current study investigates a new approach for biogas upgrading, and increase of total CH4 in conjunction with buffering acidification by using zero-valent iron (powder and scrap metals at concentrations 25, 50, and 100 g/L) in anaerobic granular sludge and cheese whey under mesophilic batch conditions. During the first 2 cycles (total 34 days), a high performance was found in anaerobic bottles with 25 g/L powder zero valent iron (PZVI) and 50 g/L scrap zero valent iron (SZVI) since they had a higher total CH4 production compared to anaerobic bottles free of ZVI, as well as 97% CH4 composition in produced biogas compared to 74% CH4 for anaerobic bottles free of ZVI. Under these conditions, no additional NaOH was added to anaerobic bottles with 25 g/L PZVI and 50 g/L SZVI to increase the pH and at the end of 2nd cycle the concentration of VFAs was substantially lower compared to the anaerobic bottles free of ZVI. However, no positive effects of ZVI in terms of alkaline buffer were found at the 3rd and 4th cycle probably due to ZVI inactivation outer surface layer. Based on the experimental findings (anaerobic bottles: (a) 25 g/L PZVI, (b) 50 g/L SZVI and (c) free of ZVI) an economic comparison for anaerobic digestion of cheese whey by large scale was contacted and pointed out that the best scenario was the anaerobic digestion by addition of 50 g/L SZVI, followed by anaerobic digestion free of ZVI and last was the anaerobic digestion by addition of 25 g/L PZVI. This study highlights a new proof of concept for in-situ biogas upgrading and alleviation of acidification by addition of 50 g/L SZVI or 25 g/L PZVI during anaerobic digestion of cheese whey.
Keywords: Acidification; Anaerobic digestion; Cheese whey; In-situ biogas upgrading; Powder zero valent iron; Scrap zero valent iron